Urgensi Pengesahan Rancangan Undang-Undang Perampasan Aset Ditinjau dari Analisis Ekonomi atas Hukum - FAKHRI RIZKI ZAENUDIN; Fokky Fuad Wasitaatmadja (CV Rewang Rencang, 2025)
Corruption is an extraordinary crime with broad impacts, weakening the national economy and public trust. The existing legal framework still relies on asset forfeiture through criminal convictions, resulting in lengthy processes and difficulties when offenders die, flee, or hide their assets. This article analyzes the urgency of enacting the Asset Forfeiture Bill as an instrument to optimize state loss recovery from corruption using a normative juridical method and Richard Posner’s Economic Analysis of Law (EAL). Through the Non-Conviction Based Asset Forfeiture (NCBAF) mechanism, state assets can be recovered more effectively and efficiently, creating deterrent effects and economic benefits for national development.